2010
DOI: 10.4303/jpm/p100803
|View full text |Cite
|
Sign up to set email alerts
|

On deformed quantum mechanical schemes and ★-value equations based on the space-space noncommutative Heisenberg-Weyl group

Abstract: We investigate the Weyl-Wigner-Gröenewold-Moyal, the Stratonovich and the Berezin group quantization schemes for the space-space noncommutative Heisenberg-Weyl group. We show that the ⋆-product for the deformed algebra of Weyl functions for the first scheme is different than that for the other two, even though their respective quantum mechanics' are equivalent as far as expectation values are concerned, provided that some additional criteria are imposed on the implementation of this process. We also show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In a more mathematical context they constitute the appropriate language to study harmonic analysis in Lie groups and, as it was shown in [2], they bridge different deformation quantization schemes. As for the latter it was also demonstrated in [3] that such bridge remains true even for the case of Noncommutative Quantum Mechanics understood as the quantum theory associated to the Lie algebra h θ 2n+1 of commutators:…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In a more mathematical context they constitute the appropriate language to study harmonic analysis in Lie groups and, as it was shown in [2], they bridge different deformation quantization schemes. As for the latter it was also demonstrated in [3] that such bridge remains true even for the case of Noncommutative Quantum Mechanics understood as the quantum theory associated to the Lie algebra h θ 2n+1 of commutators:…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, it is tempting to implement the full coherent-state formalism in the case of a Noncommutative Quantum Cosmology, where the configuration observables will be described by the algebra (1.1), in the hope that at an effective level the dynamical properties of noncommutativity suffice to generate solutions which are free of singularities. Overcomplete sets of coherent states have been constructed elsewhere for the case of noncommutative theories [3,8,9,10], where it must be emphasized that the representations used in all of these references are not equivalent and consequently the results obtained from their implementation in a given problem should differ. In the present work, however, we will opt for the use of the coherent system developed in [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, from the viewpoint of Deformation Quantization where the Moyal ⋆-product arises as a deformation of the algebra product of the Weyl symbols of quantum operator observables, has no conceptual support. Moreover, as we have shown in [14] (and references therein) a more logical noncommutative replacement for the Schrödinger equation is the ⋆-value equation involving the deformed Moyal ⋆-product of the Weyl symbol of the quantum Hamiltonian operator and the Wigner function. It may be meaningful to notice here also that in a previous work [15] of the type mentioned above, the region close to the singularity has not been explored and the wave functions have branch points which imply an undetermined behavior near the singularity, which could very well be attributed to the authors use of this unsubstantiated Moyal product in the Wheeler-de Witt equation.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the C ⋆ -algebra A, on which our approach is based, is in particular a good example of the strategy of Noncommutative Geometry, and a motivational argument for basing our approach on this formalism hinges, on a nut shell, on the theoretical observations that since physically meaningful quantities should be independent of the choice of a gauge, the concepts of gauge potentials or connections had to be incorporated into the formulation of Action base topological M space in Classical Bianchi I Cosmology is an R 3 , for which translations are isometries, whereas physical space at the Noncommutative Geometry level is described as a sort of a subjacent discrete noncommutative cellular structure (posets), we let A be the algebra of the noncommutative extended Heisenberg-Weyl group [14], G be the discrete topological group of translations in R 3 , (α, σ) the twisted action of G on A, with α denoting the map α : G → Aut(A) and σ : G × G → T (A) is a normalized 2-cocycle on G with values in the multiplicative group T of all complex numbers of unit modules, such that σ(x 1 , x 2 )σ(x 1 + x 2 , x 3 ) = σ(x 2 , x 3 )σ(x 1 , x 2 + x 3 ), x 1 , x 2 , x 3 ∈ G σ(x, 0) = σ(0, x) = 1.…”
Section: Introductionmentioning
confidence: 99%